Control of Fully Actuated Unmanned Aerial Vehicles with Actuator Saturation*. Issue 1 (July 2017) - Convens, Bryan; Merckaert, Kelly; Nicotra, Marco M.; Naldi, Roberto; Garone, Emanuele
Abstract: A natural way to control fully actuated UAVs is the use of feedback linearization. Indeed, given a sufficiently good knowledge of UAV mechanical properties, the resulting closed-loop system is linear and well-suited for further developments (e.g. impedance-based control for physical interactions). In the presence of actuator saturation, however, feedback linearization can lead to undesired and sometimes even unstable behaviors. To overcome this problem, this paper introduces a novel Explicit Reference Governor scheme which is particularly well suited for closed-loop systems with linear dynamics and nonlinear state and input constraints. The advantages of the proposed scheme are illustrated using numerical simulations.